Improving High School Students’ English Listening Skills Using Duolingo: Evidence From SMK Muhammadiyah 1 Palu - Safira Nur Farah; Suriaman Aminah; Agussatriana Agussatriana; Mukrim Mukrim (ELS Journal on Interdisciplinary Studies in Humanities, 2025)
This research aimed to investigate the effectiveness of the Duolingo application in improving the listening skills of tenth-grade students at SMK Muhammadiyah 1 Palu. The study employed a pre-experimental design with one group consisting of 20 students selected through purposive sampling. A pre-test and a post-test were administered, which included fill-in-the-blank and multiple-choice questions to measure listening performance. During the treatment, the students used the Duolingo application to practice listening in English. The results showed that the t-count value was higher than the t-table value, indicating a significant improvement in the students’ listening scores after the treatment. Therefore, the research hypothesis was accepted. In conclusion, the findings suggest that the Duolingo application can serve as an effective tool to enhance students’ English listening skills. Moreover, students reported increased motivation and engagement while using the application, which contributed to their consistent practice and improvement. This highlights the potential of integrating mobile-assisted language learning platforms like Duolingo into regular classroom activities to support traditional teaching methods.